Weed Control in Cole or Brassica Leafy Vegetables (Broccoli, Cabbage, Cauliflower, Collards, Mustard, Turnips, Kale) - William M. Stall (EDIS, 2010)
Revised! HS189, a 7-page fact sheet by William M. Stall, provides updated recommendations for weed control in cole or brassica leafy vegetable crops. Published by the UF Department of Horticultural Sciences, March 2010.